Paradoxical Figure And Application In Carita Pantun Sunda - Aris Darisman (Balong International Journal of Design, 2019)
Characterization is a reconstruction of form and meaning as a manifestation of Sundanese cultural identity. Characterization is reflected in story narratives with prose and poetic expressions. Paradoxical figures and characterizations in the carita pantun format give a character description that is manifested in imaginary figures. Characterization is the first step in reconstructing characters. The figure or character is an entity of Sundanese community value in which it manifests in the belief (religion), social, cultural and historical context sublimated to Carita Pantun. Pantun is not only a symbol but a sacred symbol. Generaly there’s no different between Carita pantun and the myths that exist in other countries. Carita pantun is a mythology. This study uses a qualitative method of paradoxical aesthetic approach through descriptive interpretive to provide an in-depth description and interpretation of the subject. The analysis model includes characterization analysis and paradoxical aesthetic analysis through narrative symbols on Carita pantun.